(untitled) (Medico Legal Update, 2020)
A peptic ulcer can be described as a condition in which there is a discontinuity in the entire thickness of the gastric mucosa. The discontinuity can also involve the submucosa, and in some cases, the deeper layers of the muscle wall(1). Immunological serological and molecular factors play a great role in the susceptibility and diagnosis of this disease. IL-17F genotyping were reported to have an influencing in all types of peptic ulcer. The current study aims to detect some cytokine concentration (proinflammatory and Regulatory) in patients’ blood, and some cytokine polymorphism. During the time from July 2019 to November 2019, the case-control study enrolled 318 blood samples collected from the patients who attended the Marjan Teaching Hospital- Hilla, as well as 60 healthy people. IL-17F genotyping was performing for 55 patients with peptic ulcer, and 30 healthy people as control, by using the PCR-SSP method. All types of peptic ulcers were significantly associated with IL-17F. Associations were also observed with IL-12A and IL-CXCR2. In conclusion, IL-17F, haplotypes, and genotypes have related to peptic ulcers so it can be dependent as a genetic marker for the susceptibility of this disease in Iraq